Pemaknaan masyarakat santri atas fatwa- fatwa keagamaan produk pesantren - Nasih, Ahmad Munjin (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2014)
As a Islamic educational institutions, pesantren produces not only ulamaâ who are capable to guide Muslim to the right way, but also many fatwa as solutions for Muslim community problems. This study tries to reveal how the Muslim community gives meaning of fatwa from pesantren. The results of this study shows that Muslim society vary in give meaning to fatwa. They are divided into three groups, namely: the dogmatic community, logical community, and pragmatic community. The existence of these groups is caused by education background, intensity of communication, and vested interests of the community.